Sosialisasi Penyakit Hewan Ternak dan Penanggulangannya di Desa Ciseureuh, Kecamatan Ketanggungan, Kabupaten Brebes - Muhammad Gian Gianggi Pratama; Dyfvanka Pramudya; Yuni Cahya Endrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
This community service activity aims to provide information to farmers in Ciseureuh Village, Ketanggungan District, Brebes Regency regarding common diseases of livestock and be able to apply the procedures for their handling. The main target of the socialization of livestock disease and its prevention is livestock farmers in Cisereuh Village. This activity is carried out with direct exposure to the material. Based on the results of the activities that have been carried out, the participants, especially the breeders, were very enthusiastic in listening to the socialization material and played an active role during the question and answer process regarding diseases infected by farmers and potential diseases in Cisereuh Village, as well as how to handle them. After the socialization of livestock diseases and its prevention activities are held, farmers get a lot of new knowledge about the diseases commonly experienced by livestock and farmers are able to apply how to overcome them, so that the reduction of diseased cattle and livestock that have died from diseases that are not handled properly. Keywords: livestock, livestock diseases, breeders